Determining the inhibitor content of transformer insulating oil using UV-Vis spectroscopy - Sing L.Y.; Ker P.J.; Jamaludin M.Z.; Ismail A.; Abdullah F.; Mun L.H.; Saniyyat C.N.; Shukri M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control systems; Electric transformer testing; Fourier transform infrared spectroscopy; Infrared devices; Insulating oil; Insulation; Power transformers; Ultraviolet visible spectroscopy; Conventional methods; Inhibitor Content; Naturally occurring; Optical detection; Single wavelength; UV-vis spectroscopy; Visible near-infrared; Weight percentages; Oil filled transformers